Insufficiencies of the Single Exponential Model and Efficiency of the Double Exponential Model in the Optimization of Solar Cells Efficiency - A. Zerga; B. Benyoucef; J.-P. Charles (Active and Passive Electronic Components)
Single and double exponential models are confronted to determine the most adapted model for optimization of solar cells efficiency. It is shown that the single exponential model (SEM) presents some insufficiencies for efficiency optimization. The interest of the double exponential model to optimize the efficiency and to achieve an adequate simulation of the operation of solar cells is demonstrated by means of I-V characteristics plotting.